Pengaruh Logo, Color Palette Dan Desain Feeds Instagram Terhadap Brand Awareness: Studi Empiris Pelanggan Fomo Vapestore Bogor - MD. Yuwansyah; Anton Widio Pratomo; Sri Mulyati (Jurnal Aplikasi Bisnis Kesatuan, 2026)
Fomo Vapestore is a retail business engaged in the sale of vape products and accessories, located in Bogor. In response to increasing business competition, Fomo Vapestore utilizes visual elements such as logo, color palette, and Instagram feed design to build brand identity and enhance brand awareness. The purpose of this study is to examine the effect of logo, color palette, and Instagram feed design on consumer brand awareness. This study employs a quantitative approach with a descriptive-associative method. Data were collected through questionnaires distributed to 180 respondents using purposive sampling. The data were analyzed using SmartPLS 4.0. The results show that all three independent variables have a positive and significant effect on brand awareness. The coefficient values for each variable are as follows: logo (0.308), color palette (0.454), and Instagram feed design (0.162), with significance values below 0.05. The model’s R-square value is 0.744, indicating that 74.4% of the variation in brand awareness can be explained by the three variables. These findings indicate that well-designed visual elements such as logos, color palettes, and Instagram feed designs can effectively increase consumer brand awareness of Fomo Vapestore. Therefore, the consistent use of visual identity is highly recommended in digital marketing strategies.